Model komunikasi dua arah terhadap peningkatan daya saing pondok pesantren - Alawi, Kusoy; Anggrayni, Dewi; Siregar, Nur Choiro; Ibdalsyah (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
A two-way communication model is a process of information exchange that involves reciprocal interaction between the sender and receiver of a message, in which both parties actively provide feedback to ensure clarity, understanding, and effectiveness of communication. This study aims to develop a relevant and applicable two-way communication model to enhance the competitiveness of Islamic boarding schools, particularly in the context of accepting new students and strengthening public trust. The research method uses a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, and Disseminate), combined with James E. Grunig's theory of two-way symmetrical communication. The study was conducted at two Islamic boarding schools in Sukabumi, West Java: Darussyifa YASPIDA, representing the Salafiyah typology, and Pondok Pesantren Assalam, representing the Khalafiyah typology. The model development process involved stages of needs identification, concept design, prototype testing, and dissemination of results. The model was validated by communication experts and boarding school practitioners, who indicated a very high level of feasibility based on criteria of effectiveness, relevance, and sustainability.  The final model emphasizes the principles of equality, participatory dialogue, and the strengthening of Islamic values as its main foundation. The implications of developing this model show significant potential in improving transparency, participation, and building public trust, which in turn can strengthen the competitiveness of Islamic boarding schools in accepting new students. Further research is recommended to test the application of this model in various Islamic educational institutions with more diverse regional, cultural, and typological characteristics to assess its consistency and effectiveness in a broader context.  Abstrak Model komunikasi dua arah merupakan suatu proses pertukaran informasi yang melibatkan interaksi timbal balik antara pengirim dan penerima pesan, di mana kedua belah pihak secara aktif memberikan umpan balik untuk memastikan kejelasan, pemahaman, dan efektivitas komunikasi. Penelitian ini bertujuan untuk mengembangkan model komunikasi dua arah yang relevan dan aplikatif guna meningkatkan daya saing pondok pesantren, khususnya dalam konteks penerimaan peserta didik baru serta penguatan kepercayaan publik. Metode penelitian menggunakan pendekatan Research and Development (R&D) dengan model 4D (Define, Design, Develop, and Disseminate), yang dikombinasikan dengan teori komunikasi dua arah simetris (Two-Way Symmetrical Communication) dari James E. Grunig. Studi dilaksanakan pada dua pondok pesantren di Sukabumi, Jawa Barat, yaitu Darussyifa YASPIDA yang merepresentasikan tipologi salafiyah dan Pondok Pesantren Assalam yang merepresentasikan tipologi khalafiyah. Proses pengembangan model melibatkan tahapan identifikasi kebutuhan, perancangan konsep, pengujian prototipe, serta diseminasi hasil. Validasi model dilakukan oleh pakar komunikasi dan praktisi pesantren, yang menunjukkan tingkat kelayakan sangat tinggi berdasarkan kriteria efektivitas, relevansi, dan keberlanjutan. Model akhir yang dihasilkan menekankan prinsip kesetaraan, dialog partisipatif, dan penguatan nilai-nilai Islam sebagai fondasi utama. Implikasi dari pengembangan model ini menunjukkan potensi signifikan dalam meningkatkan transparansi, partisipasi, serta membangun kepercayaan publik, yang pada gilirannya dapat memperkuat daya saing pondok pesantren dalam penerimaan peserta didik baru. Penelitian lanjutan disarankan untuk menguji penerapan model ini pada berbagai lembaga pendidikan Islam dengan karakteristik wilayah, budaya, dan tipologi yang lebih beragam guna menilai konsistensi efektivitasnya dalam konteks yang lebih luas.